Implementation e-learning through physics education study program learning on Self-Regulated Learning (SRL) - Evelina Astra Patriot; Pandu Jati Laksono (Universitas Sultan Ageng Tirtayasa, 2023)
The Covid-19 pandemic in Indonesia has caused various learning changes that initially used the direct learning process to become distance learning. In this research, the researcher aims to implement e-learning through introductory physics lectures in the physics education study program for prospective science teachers. The type of research used is experimental research with a one-shot case study research design. The sample in the research is a candidate for science teacher in semester 1 (one) in the physics education study program as many as 40 students. This study uses an instrument in the form of a self-regulated learning instrument with 19 questions. The results of this study indicate that the SRL indicator is independence from others as much as 73%, 70% of students in the indicator of self-confidence, 68% behave in a disciplined manner, 68% have a sense of responsibility, the ability to control themselves is 77%, and the percentage is 79 % behave on their initiative. The application of e-learning can provide opportunities for prospective science teacher students to develop and improve Self-Regulated Learning (SRL) in the basic physics lecture process. This research implies an alternative choice of learning that can be applied in basic physics lectures to support student learning independence.